Answer:
See proof below.
Explanation:
Note:
I think you mean that f(x) = (x + 3)/2, which is
and not what you wrote which means
![f(x) = x + (3)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/si4cy8z6novh2vlfskfmkh195a45oetu3t.png)
To prove that functions f(x) and g(x) are inverses of each other, you must do the composition of functions f and g, and then the composition of functions g and f. If both compositions give you the result of just x, then the functions are inverses of each other.
![f(x) = (x + 3)/(2); g(x) = 2x - 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pnc293lzr64uinbom8yc4kkowi7u5yncv4.png)
![(f \circ g)(x) = f(g(x)) = (g(x) + 3)/(2) = (2x - 3 + 3)/(2) = (2x)/(2) = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c2l3y1r9de8wfhjelhkmvx9pvq2xb1pkvk.png)
![(g \circ f)(x) = g(f(x)) = 2(f(x)) - 3 = (2(x + 3))/(2) - 3 = x + 3 - 3 = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/94ofbsbszv5npodarcu5k2z3w9qnmnbkch.png)
Since both compositions result in x, functions f(x) and g(x) are proved to be inverses of each other.